Preparation process of molybdenum-based fast-charging negative electrode material
Through the preparation process of molybdenum-based fast charging anode material, the C@Mo2C/N-C structure is used to solve the low capacity and stability problems of lithium-ion battery anode materials under high energy demand, and the improvement of high specific capacity and fast charging performance is achieved. And the process is environmentally friendly and low cost.
Patent Information
- Application Number
- CN202411178372.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional lithium-ion battery anode materials show low theoretical capacity and insufficient cycle stability under high energy demand, resulting in performance bottlenecks in lithium-ion batteries in applications.
The preparation process of molybdenum-based fast charging negative electrode material is adopted, and the synthesis of carbon material, hollow carbon spheres, MoO3, molybdenum oxalate solution and precursor Mo-PDA is formed to form a C@Mo2C/N-C structure to achieve a negative electrode with high specific surface area and pore capacity. Material.
It improves the specific capacity and fast charging performance of lithium-ion batteries, enhances electrochemical stability, reduces raw material costs, and is simple in process operation and environmentally friendly.
Smart Images

Figure CN119275254A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the preparation of a new material, and in particular to a preparation process of a molybdenum-based fast-charging negative electrode material. Background Art
[0002] As the energy consumption of lithium-ion equipment or tools continues to increase, people's requirements for the performance of lithium-ion batteries are also gradually increasing. Traditional electrode materials can no longer meet today's growing energy needs, resulting in some problems with lithium-ion batteries. In order to apply lithium-ion batteries more widely, it is necessary to achieve higher capacity and better cycle stability, and breakthroughs in electrode materials are the fundamental solution to the problem.
[0003] At present, the most widely used negative electrode materials in commercialization are silicon-carbon materials. Among them, although carbon materials mainly based on graphite have stable battery performance, their low theoretical capacity is not enough to meet the growing energy demand. Silicon materials have a huge volume change rate that seriously affects their specific applications. Among them, molybdenum-based composite materials have excellent electrochemical properties due to their unique morphology, high theoretical capacity and good electrical conductivity, and are considered to be a very promising negative electrode material for lithium-ion batteries. Summary of the invention
[0004] In view of the above problems, the present invention provides a preparation process of a molybdenum-based fast-charging negative electrode material.
[0005] The first technical purpose of the present invention is to provide a method for preparing hollow carbon spheres with high specific surface area and pore volume and excellent chemical stability.
[0006] The second technical purpose of the present invention is to provide a method for preparing a precursor Mo-PDA which has high catalytic activity, is environmentally friendly, low-cost and easy to control.
[0007] The third technical purpose of the present invention is to provide a preparation method for a molybdenum-based fast-charging negative electrode material with higher specific capacity, good fast-charging performance and strong stability.
[0008] The present invention provides a preparation method for a molybdenum-based fast-charging negative electrode material, comprising the following steps: the preparation method for a molybdenum-based fast-charging negative electrode material comprises the following steps: synthesis of carbon materials, synthesis of hollow carbon spheres, synthesis of MoO3, synthesis of molybdenum oxalate solution, synthesis of precursor Mo-PDA, and synthesis of C@Mo2C / NC.
[0009] Preferably, step (1) the synthesis of carbon material A certain amount of β-cyclodextrin and a certain amount of sodium hydroxide are measured and placed in beaker No. 1, a certain amount of ethanol and a certain amount of deionized water are measured and placed in beaker No. 2, and a stirring bar is added to stir, the solution in beaker No. 1 is slowly added into beaker No. 2, covered with plastic wrap, stirred until clear, the carrier gas is turned on, and the Venturi effect of the atomizer atomizes the mixed solution to form aerosol droplets, and then ammonia is used to push these aerosol droplets through the heating zone where dehydration and carbonization occur, and finally the generated carbon material is collected by the filter paper on the collector; Step (2) Synthesis of hollow carbon spheres The carbon material obtained in the above steps is placed in a tubular furnace and calcined by passing nitrogen, and the high-temperature calcination is maintained for a period of time, and then the temperature is naturally lowered to obtain HCSs, and the HCSs are soaked in an HF solution for a period of time and then centrifuged and washed to obtain hollow carbon spheres, and a certain amount of hollow carbon spheres are uniformly dispersed in concentrated nitric acid, and after high-temperature reflux reaction for a period of time, centrifuged, washed, dried, and collected to obtain functionalized hollow carbon spheres; Step (3) Synthesis of MoO3 A certain amount of deionized water is added to an appropriate amount of metal molybdenum powder and magnetically stirred for a period of time to make it uniformly dispersed, and then a certain amount of hydrogen peroxide is dropwise added to the molybdenum powder solution and continuously stirred, the obtained orange-red solution is allowed to stand for a period of time, transferred to an autoclave, and kept at high temperature for a period of time. After the autoclave is cooled to room temperature, a precipitate is obtained by filtration, and the precipitate is centrifuged and washed, and the centrifugation is continued for a period of time, and then washed with deionized water and anhydrous ethanol, and a final white precipitate is obtained after repeated washing cycles, and the white precipitate is dried in an oven to obtain MoO3 powder; Step (4) Synthesis of molybdenum oxalate solution Take a certain amount of MoO3 in a conical flask, add a certain amount of deionized water, ultrasonicate and stir for a period of time, add a certain amount of oxalic acid dihydrate to dissolve until it is evenly dispersed, reflux in an oil bath at high temperature, and stir the solution until it is clear; Step (5) Synthesis of Mo-PDA Precursor A certain amount of isopropanol and a certain amount of deionized water were measured and added to a beaker, and after stirring for a period of time, a small amount of the above-mentioned molybdenum oxalate clear solution was taken with a pipette and added to the beaker, and the stirring was continued for a period of time, and a certain amount of dopamine hydrochloride was added to the above-mentioned mixed solution. After ultrasonication for a period of time, the solution was transferred to a reactor, and after a hydrothermal reaction at high temperature for a period of time, the product was centrifuged and vacuum dried for a period of time to obtain the precursor Mo-PDA; Step (6) Synthesis of C@Mo2C / NC A certain amount of hollow carbon spheres and a small amount of glucose are ultrasonically dispersed in a certain amount of water, a certain amount of ascorbic acid and a certain amount of precursor Mo-PDA are added and stirred for a period of time, the resulting liquid is transferred into an autoclave containing a certain amount of polytetrafluoroethylene lining, placed in an oven for high-temperature reaction and continued for a period of time, and then opened after waiting for natural cooling until completely cooled. The resulting product is centrifugally washed and then dried. In order to improve the crystallinity of the resulting product, the dried powder is placed in a tubular furnace in a high-temperature nitrogen atmosphere. After calcination for a period of time at a certain heating rate, the collected black powder is C@Mo2C / NC.
[0010] The first technical purpose of the present invention is achieved through the following technical solutions: Preferably, step (1) the synthesis of carbon material Measure 1-3 mL of β-cyclodextrin and 12-17 mL of ethanol, place them in beaker No. 1, measure 5-10 mL of ethanol, 5-10 mL of water and 1-5 mL of deionized water, place them in beaker No. 2, add a stirring bar to stir, slowly add the solution in beaker No. 1 into beaker No. 2, cover with plastic wrap, continue stirring for 20-25 hours until the solution is clear, turn on the carrier gas, and the Venturi effect of the atomizer atomizes the mixed solution to form aerosol droplets, and then use ammonia to push these aerosol droplets through the heating zone where dehydration and carbonization occur, and finally the generated carbon material is collected by filter paper on the collector.
[0011] The advantages of the present invention are low raw material cost, simple operation and easy control by using solution polymerization method, and easy modification. By adjusting the conditions in the synthesis process, the performance control and modification of the carbon material can be achieved.
[0012] Preferably, step (2) the synthesis of hollow carbon spheres The product carbon material obtained in the above steps is placed in a tubular furnace and calcined by passing nitrogen. The calcination is maintained at a high temperature of 600-700°C for 1-5 hours with a heating rate of 1-5°C / min, and then the temperature is naturally lowered to obtain HCSs. The HCSs are soaked in a HF solution with a mass fraction of 10-30% for 20-25 hours, and then centrifuged and washed to obtain hollow carbon spheres. 0.1-0.5 g of the hollow carbon spheres are uniformly dispersed in 10-50 mL of concentrated nitric acid. After a high temperature reflux reaction at 70-100°C for 5-10 hours, the functionalized hollow carbon spheres are collected after centrifugal washing and drying.
[0013] The advantages of the present invention are that the hollow carbon spheres synthesized from the carbon material have a high specific surface area, a good void structure and a neutral environment, and both the HF solution and the concentrated nitric acid have strong activity and can react quickly with the carbon source to promote the formation of the hollow carbon spheres. The use of carbon material synthesis can reduce pollution to the environment.
[0014] The second technical purpose of the present invention is achieved through the following technical solutions: Preferably, step (3) the synthesis of MoO3 10-20 mL of deionized water is added to 1-5 g of metal molybdenum powder and magnetically stirred for 10-30 min to make it evenly dispersed, and then 10-30 mL of hydrogen peroxide is dropwise added to the above solution and stirred continuously. The obtained orange-red solution is allowed to stand for 10-30 min, transferred to an autoclave, and maintained at a high temperature of 100-300 ° C for 20-25 h. After the autoclave is cooled to room temperature, the precipitate is filtered to obtain a precipitate, and the precipitate is centrifuged and washed at a centrifugal speed of 5000-10000 rpm for 5-10 min. It is then washed with deionized water and anhydrous ethanol. After 5-10 cycles of washing, a final white precipitate is obtained, which is dried in an oven at 70-100 ° C to obtain MoO3 powder.
[0015] The advantage of adopting the present invention is that magnetic stirring can make the reactants fully contact and react quickly, thereby improving the reaction rate and conversion rate, and is conducive to obtaining uniform MoO3. After calcination, high-purity MoO3 can be obtained.
[0016] Preferably, in step (4), the synthesis of molybdenum oxalate solution is Take 1-3 g of MoO3 in a conical flask, add 30-60 mL of deionized water, ultrasonically stir for 10-30 min, add 1-5 g of oxalic acid dihydrate to dissolve until it is evenly dispersed, reflux heat in an oil bath at 70-100 °C, and stir the solution until it becomes clear.
[0017] Preferably, in step (5), the precursor Mo-PDA is synthesized 25-30 mL of isopropanol and 5-10 mL of deionized water were respectively measured and added to a beaker. After stirring for 20-30 min, 1-3 mL of the above-mentioned clear molybdenum oxalate solution was drawn into the beaker with a pipette and continued stirring for 20-30 min. 250-300 mg of dopamine hydrochloride was added to the above-mentioned mixture. After ultrasonication for 20-30 min, the solution was transferred to a reactor. After hydrothermal reaction at a high temperature of 150-200 ° C for 20-25 h, the product was centrifuged and vacuum dried for 20-25 h to obtain the precursor Mo-PDA.
[0018] The invention has the advantages that isopropanol as a solvent can provide a mild reaction environment and help the precipitation of the precursor Mo-PDA in the molybdenum oxalate clarified solution, thereby improving the purity of the product, and the product generated during the synthesis process has little impact on the environment.
[0019] The third technical objective of the present invention is achieved through the following technical solutions: Preferably, step (6) synthesis of C@Mo2C / NC 10~30 mg of hollow carbon spheres and 0.1~0.5 g of glucose were ultrasonically dispersed in 20~50 mL of water, 50~100 mg of ascorbic acid and 150~200 mg of precursor Mo-PDA were added and stirred for 20~30 min, the resulting liquid was transferred into an autoclave containing 100~150 mL of polytetrafluoroethylene lining, placed in an oven for high-temperature reaction at 150~200 ° C and continued for 20~25 h, waited for natural cooling to completely cool and then opened, the resulting product was centrifuged and washed and then dried. In order to improve the crystallinity of the resulting product, the dried powder was placed in a tubular furnace at a high-temperature nitrogen atmosphere of 500~600 ° C, and calcined for 1~3 h at a heating rate of 0.5~1 ° C / min. The collected black powder was C@Mo2C / NC.
[0020] The advantages of the present invention are that hollow carbon spheres are used as carriers to provide a larger specific surface area and pore volume, the use of natural products such as glucose and ascorbic acid is environmentally friendly, and the synthesis process is relatively simple. Calcination in a high-temperature nitrogen atmosphere can maintain stable pressure, which is conducive to the formation of a stable negative electrode material.
[0021] In summary, the present invention has the following beneficial effects: 1. The advantages of the present invention are that the cost of the raw materials used is low, the solution polymerization method is adopted, the operation is simple, and the control is easy. Moreover, the method is easy to modify. By adjusting the conditions in the synthesis process, the performance control and modification of the carbon material can be achieved; 2. The present invention has the advantages that the hollow carbon spheres synthesized from carbon materials have a high specific surface area, a good void structure and a neutral environment. Both HF solution and concentrated nitric acid have strong activity and can react quickly with the carbon source to promote the formation of hollow carbon spheres. The use of carbon materials for synthesis can reduce pollution to the environment. 3. The present invention has the advantage that the magnetic stirring can make the reactants fully contact and react quickly, thereby improving the reaction rate and conversion rate, and is conducive to obtaining uniform MoO3. After calcination, high-purity MoO3 can be obtained. 3; 4. The present invention has the advantages that isopropanol as a solvent can provide a mild reaction environment and help the precipitation of the precursor Mo-PDA in the molybdenum oxalate clarified solution, thereby improving the purity of the product, and the product produced during the synthesis process has little impact on the environment; 5. The advantages of the present invention are that the hollow carbon spheres as carriers provide a large specific surface area and pore volume, the use of natural products such as glucose and ascorbic acid is environmentally friendly, and the synthesis process is relatively simple. Calcination in a high-temperature nitrogen atmosphere can maintain stable pressure, which is conducive to the formation of a stable negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a process flow chart of a method for preparing a molybdenum-based fast-charging negative electrode material of the present invention. DETAILED DESCRIPTION
[0023] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0024] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products. Example 1
[0025] Step (1) Synthesis of carbon materials Measure 3 mL of β-cyclodextrin and 12 mL of ethanol, place them in beaker No. 1, measure 6 mL of ethanol, 8 mL of water and 4 mL of deionized water, place them in beaker No. 2, add a stirrer to stir, slowly add the solution in beaker No. 1 to beaker No. 2, cover with plastic wrap, continue stirring for 24 hours until the solution is clear, turn on the carrier gas, and the Venturi effect of the atomizer atomizes the mixed solution to form aerosol droplets, and then use ammonia to push these aerosol droplets through the heating zone where they are dehydrated and carbonized, and finally collect the generated carbon material with filter paper on the collector; Step (2) Synthesis of hollow carbon spheres The carbon material obtained in the above steps was placed in a tubular furnace and calcined by nitrogen, and the calcination was maintained at a high temperature of 600°C for 2 hours, and the heating rate was 3°C / min, and then the temperature was naturally lowered to obtain HCSs. The HCSs were soaked in a 10% HF solution by mass for 20 hours, and then centrifuged and washed to obtain hollow carbon spheres. 0.15g of the hollow carbon spheres were uniformly dispersed in 20mL of concentrated nitric acid, and refluxed at 70°C for 5 hours, and then centrifuged, washed, dried, and collected to obtain functionalized hollow carbon spheres. Step (3) Synthesis of MoO3 14 mL of deionized water was added to 2 g of metal molybdenum powder and magnetically stirred for 20 min to make it uniformly dispersed, and then 30 mL of hydrogen peroxide was added dropwise to the above solution and stirred continuously. The obtained orange-red solution was allowed to stand for 20 min, transferred to an autoclave, and kept at a high temperature of 200 ° C for 23 h. After the autoclave was cooled to room temperature, a precipitate was obtained by filtration. The precipitate was centrifuged and washed at a centrifugal speed of 6000 rpm for 7 min, and then washed with deionized water and anhydrous ethanol. After 8 cycles of washing, a final white precipitate was obtained, which was dried in an oven at 90 ° C to obtain MoO3 powder; Step (4) Synthesis of molybdenum oxalate solution Take 2g of MoO3 in a conical flask, add 40mL of deionized water, ultrasonicate and stir for 20min, add 3g of oxalic acid dihydrate to dissolve until it is evenly dispersed, reflux in an oil bath at 80℃, and stir until the solution is clear; Step (5) Synthesis of Mo-PDA precursor 26 mL of isopropanol and 7 mL of deionized water were measured and added to a beaker. After stirring for 20 min, 2 mL of the above-mentioned clear molybdenum oxalate solution was pipetted into the beaker and continued to stir for 30 min. 260 mg of PDA was added to the above-mentioned mixed solution. After ultrasonication for 30 min, the solution was transferred to a reactor. After hydrothermal reaction at a high temperature of 180 ° C for 25 h, the product was centrifuged and vacuum dried for 24 h to obtain the precursor Mo-PDA. Step (6) Synthesis of C@Mo2C / NC 10 mg of hollow carbon spheres and 0.2 g of glucose were ultrasonically dispersed in 30 mL of water, 50 mg of ascorbic acid and 160 mg of precursor Mo-PDA were added and stirred for 25 min, the resulting liquid was transferred to an autoclave containing 120 mL of polytetrafluoroethylene lining, placed in an oven for high-temperature reaction at 180 ° C and continued for 22 h, waited for natural cooling until completely cooled and then opened, the product was centrifuged and washed and then dried. In order to improve the crystallinity of the product, the dried powder was placed in a tubular furnace at a high-temperature nitrogen atmosphere of 600 ° C and calcined for 1 h at a heating rate of 0.6 ° C / min, and the collected black powder was C@Mo2C / NC. Example 2
[0026] Step (1) Synthesis of carbon materials Measure 2 mL of β-cyclodextrin and 14 mL of ethanol, place them in beaker No. 1, measure 7 mL of ethanol, 6 mL of water and 2 mL of deionized water, place them in beaker No. 2, add a stirrer to stir, slowly add the solution in beaker No. 1 to beaker No. 2, cover with plastic wrap, continue stirring for 22 hours until the solution is clear, turn on the carrier gas, and the Venturi effect of the atomizer atomizes the mixed solution to form aerosol droplets, and then use ammonia to push these aerosol droplets through the heating zone where they are dehydrated and carbonized, and finally collect the generated carbon material with filter paper on the collector; Step (2) Synthesis of hollow carbon spheres The carbon material obtained in the above steps was placed in a tubular furnace and calcined by nitrogen. The calcination was maintained at a high temperature of 500°C for 3 hours with a heating rate of 4°C / min, and then the temperature was naturally lowered to obtain HCSs. The HCSs were soaked in a 20% HF solution by mass for 22 hours, and then centrifuged and washed to obtain hollow carbon spheres. 0.2 g of the hollow carbon spheres were uniformly dispersed in 30 mL of concentrated nitric acid, and refluxed at 80°C for 2 hours, and then centrifuged, washed, dried, and collected to obtain functionalized hollow carbon spheres. Step (3) Synthesis of MoO3 15 mL of deionized water was added to 3 g of metal molybdenum powder and magnetically stirred for 25 minutes to make it uniformly dispersed, and then 20 mL of hydrogen peroxide was added dropwise to the above solution and stirred continuously. The obtained orange-red solution was allowed to stand for 10 minutes, transferred to an autoclave, and kept at a high temperature of 250°C for 24 hours. After the autoclave was cooled to room temperature, a precipitate was obtained by filtration, and the precipitate was centrifuged and washed at a centrifugal speed of 7000 rpm for 8 minutes. The precipitate was washed with deionized water and anhydrous ethanol, and the final white precipitate was obtained after 7 cycles of washing. The white precipitate was dried in an oven at 100°C to obtain MoO3 powder; Step (4) Synthesis of molybdenum oxalate solution Take 3g of MoO3 in a conical flask, add 20mL of deionized water, ultrasonicate and stir for 10min, add 2g of oxalic acid dihydrate to dissolve until it is evenly dispersed, reflux in an oil bath at 70℃, and stir until the solution is clear; Step (5) Synthesis of Mo-PDA Precursor 25 mL of isopropanol and 8 mL of deionized water were measured and added to a beaker. After stirring for 26 minutes, 1 mL of the above-mentioned clear molybdenum oxalate solution was pipetted into the beaker and continued to stir for 20 minutes. 250 mg of PDA was added to the above-mentioned mixed solution. After ultrasonication for 20 minutes, the solution was transferred to a reactor. After hydrothermal reaction at a high temperature of 160°C for 24 hours, the product was centrifuged and vacuum dried for 23 hours to obtain the precursor Mo-PDA. Step (6) Synthesis of C@Mo2C / NC 8 mg of hollow carbon spheres and 0.3 g of glucose were ultrasonically dispersed in 50 mL of water, 40 mg of ascorbic acid and 170 mg of precursor Mo-PDA were added and stirred for 26 min, the resulting liquid was transferred to an autoclave containing 130 mL of polytetrafluoroethylene lining, placed in an oven for high-temperature reaction at 160 ° C and continued for 24 h, waited for natural cooling until completely cooled and then opened, the product was centrifuged and washed and then dried. In order to improve the crystallinity of the product, the dried powder was placed in a tubular furnace at a high-temperature nitrogen atmosphere of 700 ° C and calcined for 2 h at a heating rate of 0.8 ° C / min, and the collected black powder was C@Mo2C / NC. Example 3
[0027] Step (1) Synthesis of carbon materials Measure 2 mL of β-cyclodextrin and 10 mL of ethanol, place them in beaker No. 1, measure 5 mL of ethanol, 9 mL of water and 5 mL of deionized water, place them in beaker No. 2, add a stirrer to stir, slowly add the solution in beaker No. 1 to beaker No. 2, cover with plastic wrap, continue stirring for 22 hours until the solution is clear, turn on the carrier gas, and the Venturi effect of the atomizer atomizes the mixed solution to form aerosol droplets, and then use ammonia to push these aerosol droplets through the heating zone where they are dehydrated and carbonized, and finally collect the generated carbon material with filter paper on the collector; Step (2) Synthesis of hollow carbon spheres The carbon material obtained in the above steps was placed in a tubular furnace and calcined by nitrogen, and the calcination was maintained at a high temperature of 600°C for 2 hours, and the heating rate was 3°C / min, and then the temperature was naturally lowered to obtain HCSs. The HCSs were soaked in a 10% HF solution by mass for 20 hours, and then centrifuged and washed to obtain hollow carbon spheres. 0.15g of the hollow carbon spheres were uniformly dispersed in 40mL of concentrated nitric acid, and refluxed at 60°C for 2 hours, and then centrifuged, washed, dried, and collected to obtain functionalized hollow carbon spheres. Step (3) Synthesis of MoO3 11 mL of deionized water was added to 3 g of metal molybdenum powder and magnetically stirred for 26 minutes to make it uniformly dispersed, and then 27 mL of hydrogen peroxide was added dropwise to the above solution and stirred continuously. The obtained orange-red solution was allowed to stand for 25 minutes, transferred to an autoclave, and kept at a high temperature of 240°C for 21 hours. After the autoclave was cooled to room temperature, a precipitate was obtained by filtration, and the precipitate was centrifuged and washed at a centrifugal speed of 7000 rpm for 5 minutes, and then washed with deionized water and anhydrous ethanol. After 5 cycles of washing, a final white precipitate was obtained, which was dried in an oven at 100°C to obtain MoO3 powder; Step (4) Synthesis of molybdenum oxalate solution Take 5g of MoO3 in a conical flask, add 50mL of deionized water, ultrasonicate and stir for 30min, add 2g of oxalic acid dihydrate to dissolve until it is evenly dispersed, reflux in an oil bath at 100℃, and stir until the solution is clear; Step (5) Synthesis of Mo-PDA Precursor 27 mL of isopropanol and 5 mL of deionized water were measured and added to a beaker. After stirring for 26 min, 3 mL of the above-mentioned clear molybdenum oxalate solution was pipetted into the beaker and stirred for 26 min. 290 mg of PDA was added to the above-mentioned mixed solution. After ultrasonic treatment for 27 min, the solution was transferred to a reactor. After hydrothermal reaction at a high temperature of 160 ° C for 23 h, the product was centrifuged and vacuum dried for 22 h to obtain the precursor Mo-PDA. Step (6) Synthesis of C@Mo2C / NC 6 mg of hollow carbon spheres and 0.5 g of glucose were ultrasonically dispersed in 30 mL of water, 70 mg of ascorbic acid and 180 mg of precursor Mo-PDA were added and stirred for 28 min, the resulting liquid was transferred to an autoclave containing 110 mL of polytetrafluoroethylene lining, placed in an oven for high-temperature reaction at 190 ° C and continued for 24 h, waited for natural cooling until completely cooled and then opened, the product was centrifuged and washed and then dried. In order to improve the crystallinity of the product, the dried powder was placed in a tubular furnace at a high-temperature nitrogen atmosphere of 900 ° C and calcined for 2 h at a heating rate of 0.8 ° C / min, and the collected black powder was C@Mo2C / NC. Example 4
[0028] Step (1) Synthesis of carbon materials 5 mL of β-cyclodextrin and 7 mL of ethanol were measured and placed in beaker No. 1. 2 mL of ethanol, 10 mL of water and 9 mL of deionized water were measured and placed in beaker No. 2. A stirring bar was added to stir the mixture. The solution in beaker No. 1 was slowly added to beaker No. 2. The mixture was covered with plastic wrap and stirred for 24 hours until the solution was clear. The carrier gas was turned on. The Venturi effect of the atomizer atomized the mixed solution to form aerosol droplets. Ammonia was then used to push the aerosol droplets through the heating zone where they were dehydrated and carbonized. Finally, the carbon material produced was collected by the filter paper on the collector. Step (2) Synthesis of hollow carbon spheres The carbon material obtained in the above steps was placed in a tubular furnace and calcined by nitrogen, and calcined at a high temperature of 900°C for 5 hours with a heating rate of 4°C / min, and then naturally cooled to obtain HCSs. The HCSs were soaked in a 30% HF solution by mass for 25 hours, and then centrifuged and washed to obtain hollow carbon spheres. 0.3 g of the hollow carbon spheres were uniformly dispersed in 20 mL of concentrated nitric acid, and refluxed at 90°C for 4 hours, and then centrifuged, washed, dried, and collected to obtain functionalized hollow carbon spheres. Step (3) Synthesis of MoO3 15 mL of deionized water was added to 4 g of metal molybdenum powder and magnetically stirred for 26 minutes to make it uniformly dispersed, and then 30 mL of hydrogen peroxide was added dropwise to the above solution and stirred continuously. The obtained orange-red solution was allowed to stand for 21 minutes, transferred to an autoclave, and kept at a high temperature of 240°C for 23 hours. After the autoclave was cooled to room temperature, a precipitate was obtained by filtration, and the precipitate was centrifuged and washed at a centrifugal speed of 9000 rpm for 9 minutes, and then washed with deionized water and anhydrous ethanol. After 5 cycles of washing, a final white precipitate was obtained, which was dried in an oven at 60°C to obtain MoO3 powder; Step (4) Synthesis of molybdenum oxalate solution Take 1g of MoO3 in a conical flask, add 30mL of deionized water, ultrasonicate and stir for 20min, add 5g of oxalic acid dihydrate to dissolve until it is evenly dispersed, reflux in an oil bath at 70℃, and stir until the solution is clear; Step (5) Synthesis of Mo-PDA Precursor 28 mL of isopropanol and 7 mL of deionized water were measured and added to a beaker. After stirring for 28 min, 2 mL of the above-mentioned clear molybdenum oxalate solution was pipetted into the beaker and continued to stir for 29 min. 300 mg of PDA was added to the above-mentioned mixed solution. After ultrasonication for 25 min, the solution was transferred to a reactor. After hydrothermal reaction at a high temperature of 190 ° C for 24 h, the product was centrifuged and vacuum dried for 23 h to obtain the precursor Mo-PDA. Step (6) Synthesis of C@Mo2C / NC 9 mg of hollow carbon spheres and 0.8 g of glucose were ultrasonically dispersed in 28 mL of water, 60 mg of ascorbic acid and 190 mg of precursor Mo-PDA were added and stirred for 30 min, the resulting liquid was transferred into an autoclave containing 130 mL of polytetrafluoroethylene lining, placed in an oven for high-temperature reaction at 200 ° C and continued for 22 h, waited for natural cooling until completely cooled and then opened, the product was centrifuged and washed and then dried. In order to improve the crystallinity of the product, the dried powder was placed in a tubular furnace at a high-temperature nitrogen atmosphere of 1000 ° C and calcined at a heating rate of 0.9 ° C / min for 4 h. The collected black powder was C@Mo2C / NC. Comparative Example 1
[0029] Step (1) Synthesis of carbon materials 5 mL of β-cyclodextrin and 7 mL of ethanol were measured and placed in beaker No. 1. 2 mL of ethanol, 10 mL of water and 9 mL of deionized water were measured and placed in beaker No. 2. A stirring bar was added to stir the mixture. The solution in beaker No. 1 was slowly added to beaker No. 2. The mixture was covered with plastic wrap and stirred for 24 hours until the solution was clear. The carrier gas was turned on. The Venturi effect of the atomizer atomized the mixed solution to form aerosol droplets. Ammonia was then used to push the aerosol droplets through the heating zone where they were dehydrated and carbonized. Finally, the carbon material produced was collected by the filter paper on the collector. Step (2) Synthesis of hollow carbon spheres The carbon material obtained in the above steps was placed in a tubular furnace and calcined by nitrogen, and calcined at a high temperature of 900°C for 5 hours with a heating rate of 4°C / min, and then naturally cooled to obtain HCSs. The HCSs were soaked in a 30% HF solution by mass for 25 hours, and then centrifuged and washed to obtain hollow carbon spheres. 0.3 g of the hollow carbon spheres were uniformly dispersed in 20 mL of concentrated nitric acid, and refluxed at 90°C for 4 hours, and then centrifuged, washed, dried, and collected to obtain functionalized hollow carbon spheres. Step (3) Synthesis of MoO3 15 mL of deionized water was added to 4 g of metal molybdenum powder and magnetically stirred for 26 minutes to make it uniformly dispersed, and then 30 mL of hydrogen peroxide was added dropwise to the above solution and stirred continuously. The obtained orange-red solution was allowed to stand for 21 minutes, transferred to an autoclave, and kept at a high temperature of 240°C for 23 hours. After the autoclave was cooled to room temperature, a precipitate was obtained by filtration, and the precipitate was centrifuged and washed at a centrifugal speed of 9000 rpm for 9 minutes, and then washed with deionized water and anhydrous ethanol. After 5 cycles of washing, a final white precipitate was obtained, which was dried in an oven at 60°C to obtain MoO3 powder; Step (4) Synthesis of C@MoO2 20 mg HCSs and 0.36 g glucose were ultrasonically dispersed in 40 mL water, 80 mg ascorbic acid and 160 mg MoO3 were added and stirred for 30 min, the resulting liquid was transferred into a 100 mL polytetrafluoroethylene-lined autoclave and placed in an oven for reaction. The reaction conditions were maintained at 200 °C for 12 h, and then opened after natural cooling until completely cooled. The product was centrifuged, washed and dried. In order to improve the crystallinity of the product, the dried powder was placed in a tubular furnace at 550 °C in a nitrogen atmosphere and calcined for 1 h at a heating rate of 0.5 °C / min, and the black powder was collected to obtain C@MoO2. Comparative Example 2
[0030] Step (1) Synthesis of molybdenum oxalate solution Take 1g of MoO3 in a conical flask, add 30mL of deionized water, ultrasonicate and stir for 20min, add 5g of oxalic acid dihydrate to dissolve until it is evenly dispersed, reflux in an oil bath at 70℃, and stir until the solution is clear; Step (2) Synthesis of Mo-PDA precursor 28 mL of isopropanol and 7 mL of deionized water were measured and added to a beaker. After stirring for 28 min, 2 mL of the above-mentioned clear molybdenum oxalate solution was pipetted into the beaker and continued to stir for 29 min. 300 mg of PDA was added to the above-mentioned mixed solution. After ultrasonication for 25 min, the solution was transferred to a reactor. After hydrothermal reaction at a high temperature of 190 ° C for 24 h, the product was centrifuged and vacuum dried for 23 h to obtain the precursor Mo-PDA. Step (3) Preparation of Mo2C / NC A certain amount of precursor product Mo-PDA was ground and calcined at 700 °C for 2 h in a hydrogen-argon mixed protective gas with a gas content of 5% at a heating rate of 2 °C / min. After natural cooling, the Mo2C / NC negative electrode material was obtained.
[0031] Comparison of detection experiments: The negative electrode materials obtained in Examples 1 to 4 and the comparative products 1 and 2 were tested. The specific testing method is as follows: Electrochemical performance test The prepared negative electrode materials were assembled in a glove box to measure the electrochemical performance by assembling a 2032 button half-cell, during which the water and oxygen content was less than 0.5 ppm, and then the working electrode was composed of a molybdenum-based negative electrode material, a binder CMC, and a conductive agent super-P in a mass ratio of 8:1:1. 20 wt% of acetylene black was used as a conductive additive, and 10 wt% of polyvinylidene fluoride was used as a binder, and then they were mixed and evenly ground in a mortar, and then placed in a small glass bottle and stirred for 12 h with an appropriate amount of N-methylpyrrolidone. The loading of the negative electrode composite on the copper current collector was maintained at 1.4 mg cm -2 Lithium was used as the reference electrode. The separator was selected from a microporous polypropylene membrane of Celgard 2400 type, and the electrolyte was a 1 mol / L LiPF6 ethyl carbonate / diethylene carbonate (EC / DEC, volume ratio 1:1) solution. The constant current charge and discharge tests were performed in a LANDCT-2001A (Wuhan, China) test system with current densities of 0.2C and 1C and a voltage range of 0.01 V to 3 V (Li / Li + ). The electrochemical impedance spectroscopy (EIS) test was carried out on an electrochemical workstation (Autolab302N) with a frequency range of 0.1 Hz to 100 KHz and an AC amplitude of 10 mV.
[0032] Table 1 Resistivity test results
[0033] As shown in Table 1, Example 3 is the best and the comparative example is relatively poor. Thanks to the high conductivity and low volume expansion rate brought by the double carbon layer structure of C@Mo2C / NC, C@Mo2C / NC has a better performance as the negative electrode of lithium-ion batteries.
[0034] Table 2 Initial discharge specific capacity test results
[0035] Table 3 Initial charge specific capacity test results
[0036] As shown in Tables 2 and 3, compared with the low-capacity Mo2C / NC anode, the C@Mo2C / NC anode has a higher discharge specific capacity, indicating that the nanotube structure with a larger aspect ratio can shorten the migration path of ions in the electrolyte, and the conductive network formed by the interconnected multidimensional porous nanostructure can improve the Li + and electron migration rate, and the larger specific surface area helps to provide more lithium active sites.
[0037] Table 4 Charge and discharge test results
[0038] From the results in Table 4, it can be seen that the coulombic efficiency of Example 4 is the best. After a certain volume change, the electrode charge and discharge reaction reaches equilibrium, the SEI film tends to be stable, the carbon protective layer and the nanostructure provide a double buffer for silicon, and the reversible capacity is stable; the comparative example is lower because the mesoporous nitrogen-doped carbon nanotube framework can act as a protective layer to inhibit the agglomeration of Mo2C nanoparticles, relieve volume strain, and further enhance the overall electronic conductivity of the material.
[0039] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A preparation process of a molybdenum-based fast-charging negative electrode material, characterized in that: Synthesis of carbon materials, synthesis of hollow carbon spheres, synthesis of MoO3, synthesis of molybdenum oxalate solution, synthesis of precursor Mo-PDA, and synthesis of C@Mo2C / NC.
2. The preparation process of the molybdenum-based fast-charging negative electrode material according to claim 1, characterized in that: Step (1) Synthesis of carbon materials A certain amount of β-cyclodextrin and a certain amount of sodium hydroxide are measured and placed in beaker No. 1, a certain amount of ethanol and a certain amount of deionized water are measured and placed in beaker No. 2, and a stirring bar is added to stir, the solution in beaker No. 1 is slowly added into beaker No. 2, covered with plastic wrap, stirred until clear, the carrier gas is turned on, and the Venturi effect of the atomizer atomizes the mixed solution to form aerosol droplets, and then ammonia is used to push these aerosol droplets through the heating zone where dehydration and carbonization occur, and finally the generated carbon material is collected by the filter paper on the collector; Step (2) Synthesis of hollow carbon spheres The carbon material obtained in the above steps is placed in a tubular furnace and calcined by passing nitrogen, and the high-temperature calcination is maintained for a period of time, and then the temperature is naturally lowered to obtain HCSs, and the HCSs are soaked in an HF solution for a period of time and then centrifuged and washed to obtain hollow carbon spheres, and a certain amount of hollow carbon spheres are uniformly dispersed in concentrated nitric acid, and after high-temperature reflux reaction for a period of time, centrifuged, washed, dried, and collected to obtain functionalized hollow carbon spheres; Step (3) Synthesis of MoO3 A certain amount of deionized water is added to an appropriate amount of metal molybdenum powder and magnetically stirred for a period of time to make it uniformly dispersed, and then a certain amount of hydrogen peroxide is dropwise added to the molybdenum powder solution and continuously stirred, the obtained orange-red solution is allowed to stand for a period of time, transferred to an autoclave, and kept at high temperature for a period of time. After the autoclave is cooled to room temperature, a precipitate is obtained by filtration, and the precipitate is centrifuged and washed, and the centrifugation is continued for a period of time, and then washed with deionized water and anhydrous ethanol, and a final white precipitate is obtained after repeated washing cycles, and the white precipitate is dried in an oven to obtain MoO3 powder; Step (4) Synthesis of molybdenum oxalate solution Take a certain amount of MoO3 in a conical flask, add a certain amount of deionized water, ultrasonicate and stir for a period of time, add a certain amount of oxalic acid dihydrate to dissolve until it is evenly dispersed, reflux in an oil bath at high temperature, and stir the solution until it is clear; Step (5) Synthesis of Mo-PDA precursor A certain amount of isopropanol and a certain amount of deionized water were measured and added to a beaker, and after stirring for a period of time, a small amount of the above-mentioned molybdenum oxalate clear solution was taken with a pipette and added to the beaker, and the stirring was continued for a period of time, and a certain amount of dopamine hydrochloride was added to the above-mentioned mixed solution. After ultrasonication for a period of time, the solution was transferred to a reactor, and after a hydrothermal reaction at high temperature for a period of time, the product was centrifuged and vacuum dried for a period of time to obtain the precursor Mo-PDA; Step (6) Synthesis of C@Mo2C / NC A certain amount of hollow carbon spheres and a small amount of glucose are ultrasonically dispersed in a certain amount of water, a certain amount of ascorbic acid and a certain amount of precursor Mo-PDA are added and stirred for a period of time, the resulting liquid is transferred into an autoclave containing a certain amount of polytetrafluoroethylene lining, placed in an oven for high-temperature reaction and continued for a period of time, and then opened after waiting for natural cooling until completely cooled. The resulting product is centrifugally washed and then dried. In order to improve the crystallinity of the resulting product, the dried powder is placed in a tubular furnace in a high-temperature nitrogen atmosphere. After calcination for a period of time at a certain heating rate, the collected black powder is C@Mo2C / NC.
3. The preparation process of a molybdenum-based fast-charging negative electrode material according to claim 2, characterized in that: Step (1) Synthesis of carbon materials Measure 1-3 mL of β-cyclodextrin and 12-17 mL of ethanol, place them in beaker No. 1, measure 5-10 mL of ethanol, 5-10 mL of water and 1-5 mL of deionized water, place them in beaker No. 2, add a stirring bar to stir, slowly add the solution in beaker No. 1 into beaker No. 2, cover with plastic wrap, continue stirring for 20-25 hours until the solution is clear, turn on the carrier gas, and the Venturi effect of the atomizer atomizes the mixed solution to form aerosol droplets, and then use ammonia to push these aerosol droplets through the heating zone where dehydration and carbonization occur, and finally the generated carbon material is collected by filter paper on the collector.
4. The process for preparing a molybdenum-based fast-charging negative electrode material according to claim 3, characterized in that: Step (2) Synthesis of hollow carbon spheres The product carbon material obtained in the above steps is placed in a tubular furnace and calcined by passing nitrogen. The calcination is maintained at a high temperature of 600-700°C for 1-5 hours with a heating rate of 1-5°C / min, and then the temperature is naturally lowered to obtain HCSs. The HCSs are soaked in a HF solution with a mass fraction of 10-30% for 20-25 hours, and then centrifuged and washed to obtain hollow carbon spheres. 0.1-0.5 g of the hollow carbon spheres are uniformly dispersed in 10-50 mL of concentrated nitric acid. After a high temperature reflux reaction at 70-100°C for 5-10 hours, the functionalized hollow carbon spheres are collected after centrifugal washing and drying.
5. The preparation process of a molybdenum-based fast-charging negative electrode material according to claim 2, characterized in that: Step (3) Synthesis of MoO3 10-20 mL of deionized water is added to 1-5 g of metal molybdenum powder and magnetically stirred for 10-30 min to make it evenly dispersed, and then 10-30 mL of hydrogen peroxide is dropwise added to the above solution and stirred continuously. The obtained orange-red solution is allowed to stand for 10-30 min, transferred to an autoclave, and maintained at a high temperature of 100-300 ° C for 20-25 h. After the autoclave is cooled to room temperature, the precipitate is filtered to obtain a precipitate, and the precipitate is centrifuged and washed at a centrifugal speed of 5000-10000 rpm for 5-10 min. It is then washed with deionized water and anhydrous ethanol. After 5-10 cycles of washing, a final white precipitate is obtained, which is dried in an oven at 70-100 ° C to obtain MoO3 powder.
6. The process for preparing a molybdenum-based fast-charging negative electrode material according to claim 5, characterized in that: Step (4) Synthesis of molybdenum oxalate solution Take 1-3 g of MoO3 in a conical flask, add 30-60 mL of deionized water, ultrasonically stir for 10-30 min, add 1-5 g of oxalic acid dihydrate to dissolve until it is evenly dispersed, reflux heat in an oil bath at 70-100 °C, and stir the solution until it becomes clear.
7. The process for preparing a molybdenum-based fast-charging negative electrode material according to claim 6, characterized in that: Step (5) Synthesis of Mo-PDA precursor 25-30 mL of isopropanol and 5-10 mL of deionized water were respectively measured and added to a beaker. After stirring for 20-30 min, 1-3 mL of the above-mentioned clear molybdenum oxalate solution was drawn into the beaker with a pipette and continued stirring for 20-30 min. 250-300 mg of dopamine hydrochloride was added to the above-mentioned mixture. After ultrasonication for 20-30 min, the solution was transferred to a reactor. After hydrothermal reaction at a high temperature of 150-200 ° C for 20-25 h, the product was centrifuged and vacuum dried for 20-25 h to obtain the precursor Mo-PDA.
8. The process for preparing a molybdenum-based fast-charging negative electrode material according to claim 7, characterized in that: Step (6) Synthesis of C@Mo2C / NC 10~30 mg of hollow carbon spheres and 0.1~0.5 g of glucose were ultrasonically dispersed in 20~50 mL of water, 50~100 mg of ascorbic acid and 150~200 mg of precursor Mo-PDA were added and stirred for 20~30 min, the resulting liquid was transferred into an autoclave containing 100~150 mL of polytetrafluoroethylene lining, placed in an oven for high-temperature reaction at 150~200 ° C and continued for 20~25 h, waited for natural cooling to completely cool and then opened, the resulting product was centrifuged and washed and then dried. In order to improve the crystallinity of the resulting product, the dried powder was placed in a tubular furnace at a high-temperature nitrogen atmosphere of 500~600 ° C, and calcined for 1~3 h at a heating rate of 0.5~1 ° C / min. The collected black powder was C@Mo2C / NC.
Citation Information
Patent Citations
A preparation method of N-doped carbon-coated Mo2C / C functional composite material and application thereof in lithium sulfur battery
CN109037664A
Hollow submicron carbon spheres and preparation method thereof
CN110194444A
Preparation method of hollow carbon micrometer flower loaded superfine molybdenum carbide material and application of hollow carbon micrometer flower loaded superfine molybdenum carbide material to lithium sulfur battery
CN110759328A
Preparation process of negative electrode material of fast-charging lithium battery
CN117334882A